Predictors of cardiorespiratory fitness in female and male adults with different body mass index: National Health and Nutrition Examination Survey 1999–2004 dataset. (2nd January 2017) - Chen, Liang; Kuang, Jian; Pei, Jian-Hao; Chen, Hong-Mei; Chen, Zhong; Li, Zhong-Wen; Yang, Hua-Zhang; Fu, Xiao-Ying; Wang, Long; Chen, Zhi-Jiang; Lai, Shui-Qing; Zhang, Shu-Ting
Abstract: Background: The aim of this study was to explore factors affecting cardiorespiratory fitness in males and females with different body mass index (BMI). Methods: The National Health and Nutrition Examination Survey 1999–2004 data were used for this retrospective study. Estimated maximal oxygen uptake (VO2max ) is surrogate for cardiorespiratory fitness (CRF). Univariate and multivariate linear regression analyses were performed to explore whether study variables were associated with estimated VO2max stratified by gender and BMI categories. Results: A total of 3292 subjects 20–49 years of age were included in the analysis. CRF significantly decreased as BMI increased in both females and males. Ethnic difference was found in normal BMI in both genders and obese females; homocysteine was significantly negatively associated with estimated VO2max, as was total cholesterol. Obese male subjects with diabetes had a lower estimated VO2max than those without diabetes, and C-reactive protein (CRP) level and vitamin B12 level were significantly negatively associated with CRF. Female subjects with diabetes had higher estimated VO2max than those without diabetes. Folate was significantly positively correlated with estimated VO2max, whereas CRP was negatively correlated in obese female. Conclusions: There are different predictors of CRF in males and females, and in individuals with different BMI. Key messages: Different BMI classes are associated with different predictors of cardiorespiratory fitness. Indicators of cardiorespiratory fitness differ between sexes.